Adjuvant Aromatase Inhibitor Therapy in Early Breast Cancer: What Factors Lead Patients to Discontinue Treatment?. Issue 5 (September 2015) - Moscetti, Luca; Fabbri, Maria Agnese; Sperduti, Isabella; Fabrizio, Nelli; Frittelli, Patrizia; Massari, Annalisa; Pompei, Luciano; D'Auria, Giuliana; Pofi, Enrico; Ruggeri, Enzo Maria
Background: Aromatase inhibitors (AIs) are standard hormone therapy (HT) for the adjuvant treatment of postmenopausal endocrine-sensitive early breast cancer. Treatment discontinuation due to toxicity is an important issue that may help clinicians identify effective clinical interventions to allow adequate treatment duration. We reviewed the main reasons for interruption of AIs at our institution from 2006 to 2009. Methods: 236 patients treated with adjuvant AIs were eligible for analysis. Median age was 64 years (35-89), median follow-up 53 months (6-60). Prior adjuvant chemotherapy was taxane based in 47 patients and anthracycline based in 43 patients. 118 patients had received letrozole, 101 anastrozole, and 17 exemestane. Results: Twenty-four patients (10%) needed discontinuation of the first AI assigned as a result of toxicity. Grade 2/3 arthralgia was the main reason for discontinuation in 13/24 patients. No differences in the incidence of arthralgia were noted in patients who had received taxanes or anthracyclines. Headache, alopecia, itching, diffuse skin reaction, allergic reaction with hypertensive crisis, xerostomia and xerophthalmia, insomnia and somnolence were the other reasons for discontinuation. In multivariate logistic regression analysis, age (65 years) and HT were independent factors associated with the onset of arthralgia (p = 0.006 and p = 0.008, respectively; OR 2.65, 95% CI 1.32-5.31). Alternative HT (AI or tamoxifen) was offered to patients who wanted or needed to permanently interrupt the ongoing drug. Conclusions: In our analysis, 10% of patients discontinued the first AI assigned because of toxicity. Median time course of all adverse events leading to HT discontinuation was 155 days and 135 days for arthralgia. A switch to alternative HT with toxicity monitoring is a recommended option for avoiding premature and permanent interruption of an effective treatment.